Global production networks and the People's Republic of China's processing trade - Alyson Ma; Ari Van Assche; Chang Hong (Asian Development Bank Institute (ADBI), 2009)
This paper unveils a systematic pattern in the People's Republic of China's (PRC) processing trade. In a cross-section of the PRC's provinces, the average distance traveled by processing imports (import distance) is negatively correlated with the average distance traveled by processing exports (export distance). To explain this pattern, we set up a threecountry industry-equilibrium model in which heterogeneous firms from two advanced economies, East and West, sell their products in each other's markets. Each firm can use two modes to serve the foreign market. A firm can directly export its products from its home country. Alternatively, it can indirectly export to the foreign market by assembling its product in a third low-cost economy, PRC, which is located in the vicinity of East. Our model established two theoretical predictions relating the PRC's geographical location to its processing trade patterns. First, the PRC's processing exports are negatively affected by both an increase in import distance and an increase in export distance. Second, the PRC's processing exports to East Asian economies are more sensitive to export distance and less sensitive to import distance than its processing exports to non-Asian economies. We found empirical support for both predictions.
Keywords: F12; F14; F23; 330